Ciências e disciplinas : uma análise epistemológica sobre cursos de formação de professores de Matemática - Santos, Vinicius Machado Pereira dos (2014)
The research SCIENCE AND DISCIPLINES: an epistemological study about courses of mathematic teachers training was developed with the Postgraduate Program in Education in Science and Mathematics – PPGECEM, from Amazon Network of Education in Science and Mathematics – REAMEC, in UFMT, campus of Cuiabá, in the research line Teachers Training for an Education in Science and Mathematics. The research is based on studies about scientific productions – sciences – in terms of treatment given by authors like Bruno Latour, also considering the historical processes of constitution of disciplinary academics fields, scientific and scholar, resorting to studies researchers like Claude Blanckaert, Jean Boutier, Jean-Claude Passeron, André Chervel, Ivor Goodson among others. These studies elaborates theoretical-methodological tooling, for an analysis of disciplinary proposals of teachers training that teach Mathematics. The investigation is guided by the following question: what epistemological nature has disciplines of teachers training in the degree course? Were considered as researcher sources the political pedagogical projects to teachers training that teach mathematics in the campus of Cuiabá in UFMT. These proposals are found in documents such as: General Catalogs, Resolution of Higher Councils of UFMT, files from Department of Mathematics of Exact Science and Earth Institute of UFMT, proposals of interdisciplinary courses discussed within the UFMT in the 90s of XX century, as well as the Political Pedagogical Project from the Natural Sciences and Mathematics Full Degree course. We consider the research as a case study of teachers training, in the area of Mathematics Education through documents analysis. The results obtained with the investigation point to the diverse nature of knowledge involved in the teachers training that teach Mathematics in terms of axes developers of delimited courses by scientific-academic culture; higher-level scholar culture; and professional culture. Beyond this theoretical construction, the study presents elements to debate about the current theme of the elements constituents of teachers training courses.